«La critica letteraria è petulante!». Un’esperienza di insegnamento del saper fare critico - Elena Porciani (Between, 2013)
This contribution is an account of four courses in Literary Criticism and Comparative Literature I taught at the Second University of Naples. In particular, the focus of my teaching was on critical methodology and literary theory, so that students could develop skills of analysis and interpretation, and in so doing, could understand the fundamental role of literary criticism in their academic education.